ANALISIS PENGARUH IKLIM ORGANISASI, MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BMT HIRA SRAGEN - Riesky Ardi Bagaskara; Dewi Pujiani (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
In this study the authors have a goal to determine the effect of work motivation, work discipline and job satisfaction on the performance of employees in Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BMT Hira Sragen of the Department of Population and Civil Registration Surakarta either partially or simultaneously. Hypothesis in this research are: Suspected work motivation, work discipline and job satisfaction have a significant effect on the performance in Koperasi SimpanPinjam dan Pembiayaan Syariah (KSPPS) BMT Hira Sragen either partially or simultaneously. Data needed in this research is primary and secondary data where primary data is data obtained by using the questionnaire method from sample as much as 84respondents. Data analysis used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of data analysis in this study can be concluded that the motivation of work, work discipline and job satisfaction have a significant effect on theperformance of employees in Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) BMT Hira Sragen either partially or simultaneously.